Description of Patient Satisfaction Undergoing Hemodialysis at Santa Elisabeth Hospital Medan - Rotua Elvina Pakpahan; Helinida Saragih; Friska Sembiring; Ony Kristin Natalia Pasaribu (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Patient satisfaction influences their desire to return to the same place, and if they are not satisfied, they will look for another place of health, prolonged helminths will result in patients experiencing psychological disorders and will result in the decline of patients caused by the threat of death, overall economic problems and medical problems. Cognitive factors can influence the health and well-being of patients with kidney failure because patients with kidney failure can feel psychologically tired because they have to undergo hemodialysis. The aim of this research is to determine the description of patient satisfaction undergoing hemodialysis at Santa Elisabeth Hospital. The design method for clinical treatment is delscrilptilf which will analyze or observe a picture of the population of patients who underwent hemodilalization at Rulmah Hospital Santa Ellilsabelth with a sample size of 50 respondents. The total sampling technique was taken. Research Results The results of this research were to determine the description of patient satisfaction undergoing hemodialysis at Santa Elisabeth Hospital in Medan with a total of 50 respondents. Where the research uses tables and provides an explanation of the frequency distribution of characteristics based on age, gender, religion, occupation, marital status, education. And this research was obtained from primary data obtained from the respondents themselves. After the data is obtained, it is processed and the results will be analyzed using univariate analysis.